상안정맥혈전증을 동반한 경동맥해면정맥동루 - 나정호(Jeong Ho Na), 이수정(Soo Jung Lee) (Daihan angwa haghoi jabji, 2020)
목적: 안와연조직염으로 오인하였던 상안정맥혈전증을 동반한 경동맥해면정맥동루 1예를 보고하고자 한다. 증례요약: 72세 여자 환자가 3일 전부터 점점 심해지는 좌안의 통증과 부종, 충혈을 주소로 타 병원에서 안와연조직염으로 진단받고 전원되었다. 왼쪽 눈꺼풀의 부종과 처짐, 결막의 심한 부종과 충혈이 있었다. 안구운동검사에서 좌안의 외전, 내전, 하전 장애를 보였고 복시를 호소하였다. 부비동 조영 컴퓨터단층촬영에서 좌안 상안검의 부종과 외안근 비대, 상안정맥의 확장과 혈전이 관찰되었다. 뇌자기공명촬영 및 자기공명혈관조영술에서 좌측의 경동맥해면정맥동루가 의심되어 신경외과로 전과되어 뇌혈관조영술을 시행하였고, 동측의 간접형 경동맥해면정맥동루와 반대측의 직접형 경동맥해면정맥동루가 확인되어 색전술 및 스텐트삽입술을 시행 받았다. 수술 후 7일째 눈꺼풀과 결막의 부종, 복시는 사라지고, 모든 방향에서 안구운동제한은 보이지 않았다. 결론: 상안정맥혈전증은 안와연조직염과 같은 감염성 질환이 가장 흔한 원인으로 알려져 있으나 본 증례와 같이 경동맥해면정맥동루가 원인이 되는 경우도 있으므로 철저한 영상학적 검사가 증상의 빠른 호전에 중요하다. Purpose: To report a case of carotid-cavernous fistula associated with superior ophthalmic vein thrombosis which was misdiagnosed as orbital cellulitis. Case summary: A 72-year-old female was transferred to our hospital because she had been diagnosed with orbital cellulitis at another hospital due to pain, swelling, and redness of the left eye, which became increasingly severe 3 days prior to her visit. The patient had edema and ptosis of the left eyelid, severe chemosis, and congestion of the conjunctiva. The eye movement test showed limitations in abduction, adduction, and infraduction of the left eye, and the patient complained of diplopia. Paranasal sinus computed tomography showed an edema of the left upper eyelid, enlargement of the extraocular muscles, and dilation and thrombosis of the superior ophthalmic vein. On brain magnetic resonance imaging and magnetic resonance angiography, left carotid-cavernous fistula was suspected, so she was transferred to neurosurgery and a cerebral angiography was performed. Cerebral angiography showed an indirect carotid-cavernous fistula on the ipsilateral side and a direct carotid-cavernous fistula on the opposite side. The patient underwent embolization and stenting. Seven days after surgery, the eyelid and conjunctival swelling and diplopia disappeared and there was no limitation of eye movement in any direction. Conclusions: An infectious disease such as orbital cellulitis is the most common cause of superior ophthalmic vein thrombosis. However, as in this patient, carotid-cavernous fistula can be the cause, so thorough imaging is important for rapid improvement of symptoms. KCI Citation Count: 0